Self-guided versus facilitator-guided debriefing in immersive virtual reality simulation: Protocol for a randomized controlled non-inferiority trial assessing teamwork skills in medical students - Amalie Middelboe Sohlin; Anja Poulsen; Ida Madeline Hoffmann; Line Klingen Gjærde; Stine Lund; Gritt Overbeck; Lone Paulsen; Todd P. Chang; Joy Yeonjoo Lee; Jette Led Sørensen; Jesper Kjærgaard (PLoS ONE, 2025)
Simulation-based medical education has been shown to be more effective but also logistically demanding and costly compared to other educational strategies in developing medical skills. Immersive virtual reality is an emerging technology enabling learners to train without a facilitator through computer-generated feedback, offering the potential for increased flexibility in the timing and location of the training and reduced costs. However, little is known about whether immersive virtual reality simulation yields similar results with and without a facilitator. The aim of this study is to compare the effects of self-guided compared to facilitator-guided debriefing for immersive virtual reality simulation-based pediatric emergency team training. We will conduct a randomized, controlled, single-blinded non-inferiority study with a parallel group, pretest-post-test design. 88 medical students (44 teams) will be randomized to undergo immersive virtual reality simulation-based pediatric emergency team training with either self-guided or facilitator-guided debriefing. We will assess the teams before and after the virtual reality intervention in a mannequin-based simulation. The mannequin-based simulation will be videorecorded, and two independent raters, blinded to group allocation, will assess the recordings using validated scales measuring teamwork skills (primary outcome), ABCDE adherence, and time to critical actions. We will further collect data on perceptions of debriefing quality, motivation, workload, usability, and cybersickness. To account for repeated measures and clustering within teams, we will apply a linear mixed model for data analysis. This study aims to provide insight into the effects of self-guided versus facilitator-guided debriefing in immersive virtual reality simulation, with implications for the future development and implementation of immersive virtual reality simulation in medical education. We have registered the trial on ClinicalTrials.gov (identifier: NCT06956833).